Weedflower - Kadohata, Cynthia (New York Atheneum Books for Young Readers, 2006)
After twelve-year-old Sumiko and her Japanese-American family are relocated from their flower farm in southern California to an internment camp on a Mojave Indian reservation in Arizona, she helps her family and neighbors, becomes friends with a local Indian boy, and tries to hold on to her dream of owning a flower shop.
Ages 11 up.
A Junior Library Guild selection.
Keywords: Japanese Americans -- Evacuation and relocation, 1942-1945 -- Juvenile fiction; World War, 1939-1945 -- United States -- Juvenile fiction; Mohave Indians -- Juvenile fiction; Indians of North America -- Arizona -- Juvenile fiction; Japanese Americans -- Evacuation and relocation, 1942-1945 -- Fiction; World War, 1939-1945 -- United States -- Fiction; Mohave Indians -- Fiction; Indians of North America -- Arizona -- Fiction; Arizona -- History -- 1912-1950 -- Juvenile fiction; Arizona -- History -- 1912-1950 -- Fiction